PENGARUH BRAND AMBASSADOR KOREA DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN SKINCARE LOKAL DI INDONESIA - Marsha, Deni; Yani, Muhammad; Aswan, Aswan (Gapenas Publisher, 2025)
This study examines the impact of Korean celebrities as brand ambassadors and product quality on consumer purchase intention for local skincare products in Indonesia. In the growing skincare industry, employing Korean celebrities as brand ambassadors has become an effective marketing strategy, contributing to increased brand appeal and influencing consumer purchasing decisions. The study adopts a quantitative approach with a survey design, involving 100 purposively selected respondents. Data were collected through an online questionnaire using a 5-point Likert scale and analyzed through multiple linear regression. The findings reveal that Korean celebrities as brand ambassadors have a significant effect on consumer purchase intention. Additionally, product quality is identified as a key determinant in influencing purchasing decisions. Collectively, the combination of effective brand ambassadors and high product quality creates a strong synergy in driving consumer purchase intention. These findings provide strategic insights for local companies to enhance their competitiveness in the increasingly saturated skincare market. The study also highlights the importance of integrating cultural elements into marketing strategies to establish emotional connections with consumers.